The role of the aluminum industry in Azerbaijan's economy: A general overview - Ramil I. Hasanov (Business & IT, 2023)
Azerbaijan is the main oil and gas exporting country in Eastern Europe and one of the main energy suppliers in Europe. Azerbaijan, whose economy is based on the oil industry, has recently seen a certain revival in the non-oil sector. Azerbaijan is also one of the main producers of aluminum in Eastern Europe, and there are partnerships with Europe in the development of this industry as well as in the energy sector. The development of the non-oil sector in Azerbaijan is essential for the country's economy. This sector is heavily dominated by the aluminum industry. As part of the research, an economic analysis review of the Azerbaijani aluminum industry in the non-oil sector is implemented. In 2022, $3 billion worth of non-oil sector products were exported from Azerbaijan to the global market; the aluminum industry accounted for more than 5% of this total. Azeraluminium LLC, the Caucasus region's sole primary aluminum producer, exports 98% of its products to countries around the world. The general platform and development of the Azerbaijani aluminum industry, the brief technological structure of the Ganja Aluminum Complex, and the future strategy and goals of this field have all been demonstrated in a concise scientific article. The main aim of this research is to analyze the Azerbaijani aluminum industry.